Analisis Kelayakan Ekonomi Pembangunan Gedung Kos Defilla Tiga Lantai Berdasarkan Data Rencana Anggaran Biaya - Insyiroh Hazhiyatil Fathinah; Amri Gunasti (Journal of Science and Engineering, 2026)
The construction of boarding house buildings is one form of property investment that has promising prospects in urban areas. This study aims to analyze the economic feasibility of the Defilla Three-Story Boarding House construction project based on the Budget Plan (RAB) data. The study uses secondary data obtained from a previous undergraduate thesis regarding the cost estimation and tender process of the Defilla Three-Story Boarding House project in Semarang. The data were further analyzed using the Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cost Ratio (BCR), and Payback Period (PP) methods. The total investment cost based on the Budget Plan data was Rp1,570,137,000. The analysis results showed an NPV value of Rp430,521,112, an IRR value of 13.91%, a BCR value of 1.27, and a Payback Period of 6 years and 8 months. Based on these results, the construction project of the Defilla Three-Story Boarding House is considered economically feasible and has the potential to provide long-term investment benefits.